Prospek Pengembangan Model Interaksi Landuse-Transportasi Berbasis Teknologi Sistem Informasi Geografis - Kusumantoro, Iwan P. (Center for Research and Community Services ITB, 1997)
Urban transportation analysis model has made great advances based on the development of computer technology. These improved capabilities will make possible for transportation analyst to deal more realistically with transportation problems and other problems in the urban spatial context. A new generation of spatial analysis models is being developed using modern GIS, such as the integration of landuse-transportation modeling based on GIS technology. This model will have a good prospect to be developed as a tool for urban spatial analysis.